Gestão da cadeia de suprimentos na indústria da construção civil: uma análise bibliométrica - Krainer, Christiane Wagner Mainardes; Krainer, Jefferson Augusto; Ribeiro, Daniel Getúlio Fernandes; Iarozinski Neto, Alfredo; Romano, Cezar Augusto (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The supply chain in the construction industry operates with many suppliers of the most varied technological and managerial characteristics. Integrating this diversity is a challenge. In this sense, studying the supplier in the supply chain can contribute to the industry's best results. This paper aims to highlight the research areas and relevant work on supply chain management in the construction industry, focusing on suppliers. Thus, a bibliometric analysis of citations and cocitation was performed with the support of the CiteSpace II tool. The raw data (publications limited to the period 1990 to 2019) were extracted from the Web of Science (WoS). Twenty research areas were identified, of which "integration" and "sustainability" were the most productive areas (most of the published works). The three most recent and promising areas were: "supplier selection", "sustainability" and "supply chain integration". As a final result, we present a panoramic map of the publications on the subject analyzed and how they are interconnected in networks (integration of works and formation of research areas). This map, among others, can instruct and mark future in-depth studies on a particular area of interest or how they relate to each other.